RETRACTED ARTICLE: Butein inhibits metastatic behavior in mouse melanoma cells through VEGF expression and translation-dependent signaling pathway regulation - Yu-Wei Lai; Shih-Wei Wang; Chien-Hsin Chang; Shih-Chia Liu; Yu-Jen Chen; Chih-Wen Chi; Li-Pin Chiu; Shiou-Sheng Chen; Allen W. Chiu; Ching-Hu Chung (BMC, 2015)
Abstract Background Melanoma is an aggressive skin cancer and a predominant cause of skin cancer-related deaths. A previous study has demonstrated the ability of butein to inhibit tumor proliferation and invasion. However, the anti-metastatic mechanisms and in vivo effects of butein have not been fully elucidated. Methods MTT cell viability assays were used to evaluate the antitumor effects of butein in vitro. Cytotoxic effects of butein were measured by lactate dehydrogenase assay. Anti-migratory effects of butein were evaluated by two-dimensional scratch and transwell migration assays. Signaling transduction and VEGF-releasing assays were measured by Western blotting and ELISA. We also conducted an experimental analysis of the metastatic potential of tumor cells injected into the tail vein of C57BL/6 mice. Results We first demonstrated the effect of butein on cell viability at non-cytotoxic concentrations (1, 3, and 10 μM). In vitro, butein was found to inhibit the migration of B16F10 cells in a concentration-dependent manner using transwell and scratch assays. Butein had a dose-dependent effect on focal adhesion kinase, Akt, and ERK phosphorylation in B16F10 cells. Butein efficiently inhibited the mTOR/p70S6K translational inhibition machinery and decreased the production of VEGF in B16F10 cells. Furthermore, the in vivo antitumor effects of butein were demonstrated using a pulmonary metastasis model. Conclusion The results of the present study indicate the potential utility of butein in the treatment of melanoma.